A Comparative Genomic Analysis of Epstein–Barr Virus Strains with a Focus on EBV2 Variability - Blazquez, Ana Catalina (2025)
Most genomic studies on Epstein-Barr virus variability have focused on geographic and pathological association of EBV1 genomes. In contrast, the variability of EBV2 genomes has been less explored, mainly due to its restricted geographic circulation and the lesser number of sequenced EBV2 isolates. In this study, we sequenced and analyzed 28 EBV1, 10 EBV2 genomes from Argentina, which were combined with 239 downloaded complete genomes from other geographic regions, to produce an initial multi-sample.vcf file comprised of 278 EBV genomes. In this context, we identified 1,093/4,541 positions in the viral genome that contribute to variability between viral types, mainly located in the EBNA2, EBNA3 family of genes and the adjacent BZLF1, BZLF2 and BLLF1 genes. We further described that this variability exhibits distinct patterns across Africa, South America, and Southeast Asia. Compared to EBV1, EBV2 genomes showed fewer variable positions relative to its reference genome (Wilcoxon test, p = 0.0001). Principal component analysis revealed that EBV2 genomes from Southeast Asia segregate independently from those from South America (Wilcoxon test, Bonferroni correction; p = 1.1 x 10-7) and Africa (Wilcoxon test, Bonferroni correction; p = 2.6 x 10-9). Additionally, we identified those precise variable positions with geographic segregation strength: 1,135/3,666 in EBV1 and 380/3,276 in EBV2. Furthermore, the distribution of variable positions along the genome disclosed a close relation for EBV2 isolates from Africa and South America as compared to isolates from Southeast Asia. Although our analysis is limited to EBV2 genomes isolated from three geographic regions, it is to the best of our knowledge, the first study to comprehensively characterize the geographic variability of the complete EBV2 genome. These findings underscore the geographic and genetic diversity of EBV2 genomes and contribute to understanding EBV´s evolutionary dynamics and potential regional adaptations. This research enhances our understanding of EBV2 genomic variability, supporting future epidemiological studies and advancing the knowledge base for targeted treatments and vaccine development for EBV-associated diseases.